การมีส่วนร่วมทางการเมืองของข้าราชการทหารอากาศ กรณีศึกษา สำนักงานผู้บังคับทหารอากาศดอนเมือง - กูลพิมาย, เทพประทาน; แสนภูมี, สมชัย (วารสาร มมร ยศสุนทรปริทรรศน์, 2025)
The research aimed to : 1) study the forms and levels of political participation of air force officials 2) compare political participation of air force officials according to personal factors using quantitative research methods. The sample group consisted of 178 air force officials working at Don Mueang Air Force Commander’s Office. The research instrument was a questionnaire. The research results found that: 1) The overall picture of political participation was at a high level (X = 4.09, S.D = 1.11). The results of pairwise comparisons found ndings from this research indicate that Air Force officers are aware of their political role, but have limitations in expressing and participating openly due to disciplinary requirements and organizational policies, which affect the overall level of political participation. The information obtained from this research can be used as a guideline for developing practices and policies to promote political participation of air force officers appropriately and in accordance with democratic principles. Keywords: political participation, air force officers, participation patternsguideline for developing practices and policies to promote political participation of Air Force officers appropriately and in accordance with democratic principles.